Aerosol propellants leading to factitious reading by gas monitoring - Adabala, Vijay; Gupta, Priyanka (Bali Journal of Anesthesiology, 2019)
A well-equipped Anaesthesia workstation is boon for safe anaesthesia practice. Anaesthesia agent gas monitoring has become an integral part of intraoperative monitoring. The infrared analyzers are commonly used for measuring anaesthetic agents. These advanced gas monitoring devices help in accurate titration of delivery of anaesthetics to patients particularly at low flows. However as with any technology, gas monitoring is also associated with inherent errors. Newer aerosol propellants like hydro-flouro- alkanes (HFA) are known to cause erroneous detection of inhalational anaesthetic agents during general anaesthesia.